PODCAST: MEMBANGUN GERAKAN ANTI-RASISME DI KALANGAN MILLENIAL - Edy Yulianto Putra; Abue Abue; Cicillia Chandra Putri; Delnecca Delnecca; Fariono Fariono; Febrine Febrine; Tjang Fang Fang; Valeria Valeria; Vina Vina; Yenny Permata Liegestu; Yvonny Yvonny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Racism is a type of discrimination against someone based on their race or it could be their ethnicity. Racism happens often because of the differences that we have between us, especially caused by physical appearance, since the race is also deeply related to physical appearance and also, in fact, based in Sociology, three main races in this world are divided into three, each characterized by their own skin color. The goal of this program is to educate society especially the young generations through Podcast media. The effect that we hope we can give with this program is the pluralism harmonization in the society of Indonesia, in the hope to materialize the third Pancasila precept which is the unity of Indonesia. With the unity in the society, Indonesia is a multicultural country that can focus to move forward together, just like the saying, united we stand, divided we fall.